Parallel Collections of Weapons and Antiquities - Shaw, Wendy (Possessors and Possessed, 2003)
During the late nineteenth century, the Ottoman museum developed out of the collections in the House of Weapons, renamed the Military Storehouse (Harbiye Anbar1) in 1839. Thus the collections remained on the grounds of the Topkap1 Palace; all but one would remain there until the end of the empire. This location played an important role in emphasizing the imperial nature of the collections, their relation to the state, and their potential audiences. The importance of the museum’s location came not so much from the immediacy of the royal family but from its proximity to the empire’s administrative offices. In 1853